Pengaruh Minat Belajar Dan Disiplin Belajar Terhadaphasil Belajar Siswa Pada Mata Pelajaran Ips Kelas VIII UPTD SMP Negeri 6 Pematang Siantar - Paris Marjaya Siallagan; Injen Pardamean Butar-butar; Paulina Herlina N Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to gain knowledge regarding the influence of learning interest and learning discipline on student learning outcomes in social studies subjects class VIII UPTD SMP Negeri 6 Pematang Siantar. This type of research is qualitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 24. The population in this study was 171 people, and the sample used was 120 people. The sampling technique used was simple random sampling. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of the research state that: 1) There is a positive and significant influence of interest in learning on student learning outcomes. This can be seen in the t test where the t value of interest in learning (2.927) > t table value (1.658096). 2) There is a positive influence of learning discipline on student learning outcomes. This result can be seen in the t test where the calculated value of student learning outcomes is (2.520) > t table (1.658096) which means that this variable has an effect. 3) Interest in learning and learning discipline together influence student learning outcomes. This result can be seen in the F test where the Fcount value (6.219) > Ftable value (2.682132). The R Square coefficient of determination test was found to be 0.098, which means 9.8% of the variables of learning interest and learning discipline on student learning outcomes in social studies subjects class VIII UPTD SMP Negeri 6 Pematang Siantar. Meanwhile, 90.2% is the influence of other variables not examined in this research.